SCIENTIFIC PARADIGM´S CHANGE AND LAW - Rearte, Martín (2013)
The purpose of this article is to reflect on the role played by the changing in the Sciences *natural and social* meaning; and in the Law Science itself. If we can understand the change in the Science meaning, it could be useful to propose a change in the Law Science meaning. It is the only way to overcome the differences between some law institutions and the reality where they must work.